A HIGH-PERFORMANCE LIQUID CHROMATOGRAPHYâ€“MASS SPECTROMETRY/MASS SPECTROMETRY METHOD DEVELOPMENT FOR THE QUANTITATIVE DETERMINATION OF BISOPROLOL FROM CACO-2 CELL MONOLAYERS - Logoyda, Liliya; Korobko, Dmytro (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: A simple, rapid high-performance liquid chromatographyâ€“mass spectrometry (MS)/MS method was developed for the determination of bisoprolol from confluent Caco-2 monolayers and from aqueous solution. Methods: Chromatography was achieved on discovery C 18, 50 mmÃ—2.1 mm, 5 Î¼m column. Samples were chromatographed in a gradient mode (eluent A [acetonitrile:water:formic acid, 5:95:0.1 v/v] and eluent B [acetonitrile:formic acid, 100:0.1 v/v]). The initial content of the eluent B is 0%, which increases linearly by 1.0 min to 100% and to 1.01 min returns to the initial 0%. The mobile phase was delivered at a flow rate of 0.400 ml/min into the mass spectrometer ESI chamber. The sample volume was 5 Î¼l. Results: Under these conditions, bisoprolol was eluted at 1.49 min. According to the Caco-2 test results, bisoprolol appeared to have moderate to high permeability. It should be noted that the recovery value for bisoprolol is 97.69%. Caco-2 permeability values for bisoprolol are in agreement with BCS Class I classification for these drugs and their known high bioavailability in humans. Conclusion: From results of analysis, it can be concluded that developed method is simple and rapid for the determination of bisoprolol from confluent Caco-2 monolayers and from aqueous solution. Acquired results demonstrate that proposed strategy can be effortlessly and advantageously applied for the examination of bisoprolol from Caco-2 cell monolayers.